2003
DOI: 10.1291/hypres.26.265
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bradykinin in Renoprotective Effects by Angiotensin II Type 1 Receptor Antagonist in Salt-Sensitive Hypertension.

Abstract: and its related organ damage is attenuation of the activation of AT1 receptors by angiotensin converting enzyme inhibitors (ACEI) or AT1 receptor antagonists (AT1A) (1, 6).Bradykinin, a product from a kininogen substrate by kallikrein action, causes vasodilatation and natriuresis through the release of nitric oxide (NO) and prostaglandins (PGs) (7). Thus far, two types of kinin G protein-coupled receptors, B1 and B2, have been characterized (8). The B2 receptor mediates the majority of the cardiovascular and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…These observations were similar to those in a previous report that showed that cardiac hypertrophy was prevented by ACE inhibitor treatment (14) or angiotensin receptor blockade (19) but not by combining either treatment with BK B2 receptor antagonist.…”
Section: Fig 8 Morphologic Changes Of Rat Coronary Vessels Sectionsupporting
confidence: 92%
“…These observations were similar to those in a previous report that showed that cardiac hypertrophy was prevented by ACE inhibitor treatment (14) or angiotensin receptor blockade (19) but not by combining either treatment with BK B2 receptor antagonist.…”
Section: Fig 8 Morphologic Changes Of Rat Coronary Vessels Sectionsupporting
confidence: 92%
“…ACEIs inhibit not only the formation of active ANGII, but also kinin degradation, thereby increasing the level of the potent vasodilator, bradykinin (BK). Despite some conflicting data (Nabokov et al, 1998), evidence is increasing that the renoprotective effects of ACEIs are mediated partly by BK B2 receptor (BK2R) activation (Yokota et al, 2003). BK2R activation reduced fibrosis in animal models of tubule-interstitial fibrosis (Seccia et al, 2006), and investigators observed increased albuminuria and glomerular sclerosis in a BK2R-deficient Akita mouse model of diabetes (Kakoki et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some results suggest that the stimulation of AT2 receptors can evoke a release of kinins from endothelial cells [35,36]. Several effects of ATI receptor antagonists are reduced or abolished by BK B 2 -antagonists suggesting the involvement of kinins [43,44]. Moreover, angiotensin-II-(1-7), the amino-terminal angiotensin heptapeptide, formed from angiotensin I by a recently discovered angiotensin-converting enzyme 2, has a kinin-like activity on the vascular system [35,36,45].…”
Section: Inhibition Of Ace Increase In Insulin Sensitivity and Kininsmentioning
confidence: 99%